2006
DOI: 10.1080/10286020500176344
|View full text |Cite
|
Sign up to set email alerts
|

Studies on chemical constituents from Ilex pubescens

Abstract: Two new phenolic glycosides, ilexpubsides A and B, along with four known lignan glycosides were isolated from the roots of Ilex pubescens. By spectral evidence, the structures of the new compounds were elucidated as 4-O-beta-D-[6'-O-(4''-O-beta-D-glucopyranosylvanilloyl)glucopyranosyl] vanillic acid (1) and syringinic 6'-O-beta-D-xylopyranoside (2). The known compounds were identified to be liriodendrin (3), (-)-olivil (4), tortoside A (5) and (+)-cyclo-olivil (6). All compounds were first isolated from Ilex p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…All the solvents were Abstract ! Eleven new triterpene saponins, ilexpublesnins C-M (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), along with ten known analogues were isolated from the roots of Ilex pubescens. Their structures were elucidated on the basis of extensive spectroscopic analysis, including 1D and 2D NMR experiments.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the solvents were Abstract ! Eleven new triterpene saponins, ilexpublesnins C-M (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), along with ten known analogues were isolated from the roots of Ilex pubescens. Their structures were elucidated on the basis of extensive spectroscopic analysis, including 1D and 2D NMR experiments.…”
Section: Instrumentsmentioning
confidence: 99%
“…Additionally, ten known analogues (12-21) (see Supporting Information) were also isolated. By comparing their 1 H and 13 C NMR as well as MS data with reported values, their structures were identified as ilexoside II (12) [22], ilexsaponin B 1 (13) [28], ilexsaponin B 3 (14) [28], ilexoside O (15) [30], ilexsaponin B 4 (16) [31], ilexoside XV (17) [32], ilexsaponin C (18) [33], chikusetusaponin IVa (19) [22], oleanolic acid 28-O-β-D-glucopyranol ester (20) [34], and pubescenoside C (21) [4]. Compounds 1, 2, 10, and 11 are considerably special, as they contain the rare 24-aldehyde group, compared to the common 23-al-…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…(Aquifoliaceae) is an evergreen shrub with a wide distribution in Southern China, and the root, called "Mao Dong Qing", has been a well known folk medicine in China for the treatment of cardiovascular disease, cerebral thrombosis, and hyperlipidemia [1]. Previous research revealed that I. pubescens is rich in triterpenoids, possessing the bioactivities of inhibiting platelet aggregation, preventing thrombosis, enlarging blood vessels, improving microcirculation, reducing cardiac ischemia, and enhancing anoxia resistance [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In addition, other species of Ilex L. are a rich resource of triterpenoids and flavonoids, with similar pharmacological activities as I. pubescens [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Among these fractions, a distinct and vivid red-purple spot from fr. 6 was isolated purified and identified as lambertianic acid (LA) with over 98% purity based on spectroscopic analyses such as NMR, MS, and IR [28].…”
Section: Lambertianic Acid Isolationmentioning
confidence: 99%